Performance pathways in elite middle- and long-distance track and field athletes: the influence of a successful youth - Brustio, P. R.; Stival, M.; Cardinale, M.; Mulasso, A.; Rainoldi, A.; Boccia, G. (Journal of Science and Medicine in Sport, 2024)
Objectives There is limited information on the performance progression of athletics endurance athletes from junior-to-senior status and the determinants of success in adulthood. This study aimed to quantify the youth-to-senior transition rate, the likelihood of success and the relationship between youth and senior performance among World-class athletes competing in middle- and long-distance disciplines.